Polska bibliografia antyku chrześcijańskiego 2024. Z uzupełnieniami za rok 2023 - Pawlak, Adam (Vox Patrum, 2025)
Every year, the journal Vox Patrum publishes a bibliography of Christian antiquity that presents the scholarly output of Polish authors from the previous year. The bibliography is organized into thirteen thematic categories and according to the names of the ancient authors to whom the publications refer.